Osteocalcin Induces Growth Hormone/Insulin-Like Growth Factor-1 System by Promoting Testosterone Synthesis in Male Mice - Li, Y.; Li, K. (Hormone and Metabolic Research, 2014)
Osteocalcin has been shown to enhance testosterone production in men. In the present study, we investigated the effects of osteocalcin on testosterone and on induction of the growth hormone/insulin-like growth factor-1 axis. Osteocalcin injection stimulated growth, which could be inhibited by castration. In addition, osteocalcin induced testosterone secretion in testes both in vivo and in vitro. Using real-time polymerase chain reaction and Western blotting, we showed that growth hormone expression was significantly increased in the pituitary after osteocalcin injection (p<0.05). Growth hormone expression in CLU401 mouse pituitary cells was also significantly stimulated (p<0.05) by osteocalcin-induced MA-10 cells. Osteocalcin injection also promoted hepatic expression of growth hormone receptor and insulin-like growth factor-1 (p<0.05), as demonstrated by real-time polymerase chain reaction and Western blotting. Similarly, osteocalcin-induced MA-10 cells promoted growth hormone receptor and insulin-like growth factor-1 expression in NCTC1469 cells. These results suggest that the growth-stimulating activities of osteocalcin are mediated by testicular testosterone secretion, and thus provide valuable information regarding the regulatory effects of osteocalcin expression on the growth hormone/insulin-like growth factor-1 axis via reproductive activities.
Keywords: osteocalcin; growth hormone; growth hormone receptor; testosterone; male